Applying Green Hotel to Enhance Service Quality of The Front Office Staff at Mercure Bali Legian - Ni Kadek Putri Wulandari; Nyoman Mastiani Nadra; Ni Ketut Bagiastuti; I Ketut Astawa; I Made Budiasa (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: This study aims to analyze the application of green hotels to improve the service quality of front office staff at Mercure Bali Legian and to identify indicators that need to be improved and maintained in the service quality of front office staff at the hotel. Research methods: The sample selection is 65 respondents and three ants, and the sampling is done by incidental sampling technique. A questionnaire is distributed to respondents. The analyticamethodue used in this research is descriptive qualitative analysis to determine the application of green hotels at Mercure Bali Legian and dynamic quantity analysis, namely imporimportance-performanceysis (IPA) yous, se d to classify service quality indicators that need to be improved and maintained into Cartesian diagram. Results and discussion: The application of green hotels has been maximally implemented by the front office staff at Mercure Bali Legian. The results of this study indicate that two indicators need to be improved in the quality of service, namely the indicator of handling guest complaints quickly and well and the indicator of staff providing information abouassistancees with environmentally friendly actions that are easy for guests to understand. Implication: There are five indicators that the front office staffs need to maintain the quality of service, namely the hotel lobby indicator is clean and smoke-free, supports the environmentally friendly concept during the check-in process by minimizing the use of paper, the staffs inform the hotel facilities including energy-saving facilities in the hotel, giving welcome drink using drinks from local products, and front office staffs providing information about the cashless program Keywords: green hotel, front office, quality of service, importance-performance analysis.